PENGARUH SIKAP KERJA, LINGKUNGAN KERJA DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN LABUHANBATU SELATAN - Supriadi . (Jurnal Prodi Fakultas Ekonomi-UISU, 2019)
The question in this study is whether there is an influence of work attitudes, working environment and the characteristics of work on a partial and simultaneous performance. The aim of the study was to analyse the influence of occupational attitudes, working environment and job characteristics on employee performance. Samples used amounted to 63 people. Data analysis methods use descriptive analysis and multiple linear regression analyses. The results of this study explain that working attitude variables, work environment and the characteristics of the work have an effect on the performance of both employees in a partial and simultaneous manner.Keywords : Attitude, Environment, Characteristics and Performance